2018
DOI: 10.1209/0295-5075/122/27001
|View full text |Cite
|
Sign up to set email alerts
|

Extended Creutz ladder with spin-orbit coupling: A one-dimensional analog of the Kane-Mele model

Abstract: We construct a topological ladder model, one-dimensional, following the steps which lead to the Kane-Mele model in two dimensions. Starting with a Creutz ladder we modify it so that the gap closure points can occur at either k = π/2 or −π/2. We then couple two such models, one for each spin channel, in such a way that time-reversal invariance is restored. We also add a Rashba spin-orbit coupling term. The model falls in the CII symmetry class. We derive the relevant 2Z topological index, calculate the phase di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…Topological invariants are available, either based on Berry phase, single-particle Green's functions, or entanglement entropy (Guo and Shen, 2011;Manmana et al, 2012;Wang et al, 2015a). Other 1D TIs are based on superlattices or Creutz-type models (Gholizadeh et al, 2018;Hetenyi and Yahyavi, 2018). As mentioned before, the topological properties can be best understood from the perspective of gapped Dirac Hamiltonians .…”
Section: One-dimensional Correlated Topological Insulatorsmentioning
confidence: 99%
“…Topological invariants are available, either based on Berry phase, single-particle Green's functions, or entanglement entropy (Guo and Shen, 2011;Manmana et al, 2012;Wang et al, 2015a). Other 1D TIs are based on superlattices or Creutz-type models (Gholizadeh et al, 2018;Hetenyi and Yahyavi, 2018). As mentioned before, the topological properties can be best understood from the perspective of gapped Dirac Hamiltonians .…”
Section: One-dimensional Correlated Topological Insulatorsmentioning
confidence: 99%
“…One version of the modified CL model concerns the case with spin-1/2 fermions and spin-orbit couplings in the ladder. Recently, such kinds of spinful CL (SCL) have been investigated in several studies [84][85][86]. It was found that the existence of spin degrees of freedom could not only modify the symmetry classification of the CL (e.g., from AIII to CII), but also induce new topological transport phenomena.…”
Section: The Modelmentioning
confidence: 99%
“…By controlling a modulation amplitude of a driving optical lattice, t 0 =t 1 condition can be achieved. [47][48][49][50]. Hence, the model has chiral, time-reversal and particle-hole symmetries.…”
mentioning
confidence: 99%